Violence Determinant on Teenagers in Yogyakarta (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2020)
Violence can adversely affect teenagers. Teenagers rarely report violence to their friends or family. Teens who are experienced with violent outbreaks have symptoms such as depression and anxiety, deviant behaviours such as smoking, drugs and alcohol and even attempted suicide. This Study used a cross-sectional design. The sample of the study were student aged 15-19 years who came from 18 Junior High School in Yogyakarta City. The study was conducted during August 2017. Sample size is 481 adolescents. Technique sampling used multistage random cluster sampling. The instrument used questionnaires on violence, knowledge, attitudes, self-confidence, family roles, peer roles, teacher roles and information sources. Data analysis used univariate and bivariate analysis used chi square test. Results showed that 77.5% of adolescents were violent and 68.4% were physically abused. Peers are a risk factor for adolescents to engage in violence (PR: 1.335; CI 95%:1.205-1.479) and families also play an important role for adolescents engaged in violence (PR: 1.179; CI 95%: 1.079-1.292). The existence of teen counseling services such as Youth Information and Counseling Center to increase adolescent insight about juvenile delinquency especially violence and impact on adolescents.